Serum MMP-8 and TIMP-1 concentrations in a population-based cohort: effects of age, gender, and health status - Julia Ranta; Aki S. Havulinna; Aki S. Havulinna; Taina Tervahartiala; Katriina Niemi; Ghazal Aarabi; Terhi Vihervaara; Veikko Salomaa; Timo Sorsa; Pirkko J. Pussinen; Pirkko J. Pussinen; Aino Salminen (Frontiers Media S.A., 2024)
BackgroundMatrix-degrading proteinases and their regulators, such as matrix metalloproteinase 8 (MMP-8) and tissue inhibitor of matrix metalloproteinase 1 (TIMP-1), may contribute to various pathological events. Elevated MMP-8 concentrations have been associated with e.g., cardiovascular diseases and periodontitis. However, there is little knowledge on the physiological concentrations of these molecules in serum, or the effect of demographic or lifestyle factors on their levels.Design and methodsWe investigated the effect of various demographic characteristics and behavioral habits, such as aging, sex, smoking, and BMI, on serum concentrations of MMP-8 and TIMP-1. We used the FINRISK97 cohort (n = 8,446), which has comprehensive information on demographic and lifestyle factors, clinical data, laboratory measurements, and register data available. Further, we investigated the concentrations of MMP-8, TIMP-1, and the MMP-8/TIMP-1 ratio in different age groups of healthy and diseased participants. A t-test was used to compare log-transformed mean levels in different groups and linear regression was used to evaluate the association between MMP-8 and TIMP-1 and selected diseases and background variables.ResultsMMP-8 levels decreased with increasing age in the whole population and for women, while TIMP-1 concentration increased slightly with age for the whole population and both genders separately (p for linear trend <0.001). The concentrations of MMP-8 were lower and TIMP-1 higher in men compared to women (p < 0.001). Additionally, a significant positive association was found for MMP-8 and smoking, CRP, and an inverse association with obesity and fasting time. For TIMP-1, significant positive associations were found with smoking, CRP and obesity, and an inverse association with prevalent diabetes.ConclusionThe association of serum MMP-8 and TIMP-1 concentrations with cardiometabolic risk is frequently investigated. MMP-8 levels decrease significantly with age and fasting time. In addition, sex, smoking, and obesity are associated with both MMP-8 and TIMP-1 concentrations. These factors should be carefully considered in epidemiological studies on serum MMP-8 and TIMP-1.